The mediating role of employee ambidexterity in the relationship between high-performance work system and employee work performance: An empirical evidence from ethio-telecom - Amare Werku Ijigu; Abebe Ejigu Alemu; Abdurezak Mohammed Kuhil (Cogent Business & Management, 2022)
A study on high-performance work systems (HPWS) has shown that there may be a gap in the relationship between HPWS and employee work performance. The reasons that are implied within such a relationship have, however, rarely been studied. Data from target employees are gathered using a census approach. 387 non-supervisory sales representatives from Ethio-Telecom in Ethiopia took part in this study, which used a cross-sectional design. By integrating social exchange theory and the AMO model, we theorized that employee ambidexterity mediates the relationship between HPWS and employee work performance. Using structural equation modeling, the findings of the study revealed that HPWS has a positive and significant effect on employee work performance. Furthermore, employee ambidexterity has a positive and significant effect on employee work performance. Finally, we found that employee ambidexterity partially mediated the positive and significant relationship between a high-performance work system and employee work performance. In order to open the mystery surrounding the relationship between HPWS and employee work performance, this study includes the mediating role of employee ambidexterity and develops a novel theoretical framework.
Keywords: 650; AMO model; employee ambidexterity; employee work performance; Ethio telecom; high-performance work system